2016
DOI: 10.5713/ajas.15.0648
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Broiler Chickens Fed Low Protein, Limiting Amino Acid Supplemented Diets Formulated Either on Total or Standardized Ileal Digestible Amino Acid Basis

Abstract: The aim of present experiment was to investigate the effect of protein reduction in commercial broiler chicken rations with incorporation of de-oiled rice bran (DORB) and supplementation of limiting amino acids (valine, isoleucine, and/or tryptophan) with ration formulation either on total amino acid (TAA) or standardized ileal digestible amino acids (SIDAA). The experimental design consisted of T1, TAA control; T2 and T3, 0.75% and 1.5% protein reduction by 3% and 6% DORB incorporation, respectively by replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…Dilger and Baker [ 16 ] came to the same conclusion and stated that the growth-depressive effect of Cys could be already alleviated by the supplementation of small amounts of Met. A negative effect of an AA imbalance on feed intake was also observed by Kumar et al [ 75 ]. Featherson and Rogler [ 18 ] suspected that an intestinal antagonism between Met and Cys causes the inferior growth at high Cys proportions.…”
Section: Discussionsupporting
confidence: 63%
“…Dilger and Baker [ 16 ] came to the same conclusion and stated that the growth-depressive effect of Cys could be already alleviated by the supplementation of small amounts of Met. A negative effect of an AA imbalance on feed intake was also observed by Kumar et al [ 75 ]. Featherson and Rogler [ 18 ] suspected that an intestinal antagonism between Met and Cys causes the inferior growth at high Cys proportions.…”
Section: Discussionsupporting
confidence: 63%
“…Considering the great interest in the use of low-CP diets in poultry nutrition, meeting the threonine, valine, and tryptophan requirements for optimal growth performance of broiler chickens is critical because these AA are considered essential AA in low-CP diets based on corn and soybean meal [ 3 , 5 , 10 , 14 , 23 ]. Waldroup et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ]. The growth retardation caused by deficiency of either individual or a combination of limiting AA such as lysine, methionine, valine, threonine, isoleucine, and tryptophan was well recognized in previous studies [ 3 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cherian (2011) fed fish and sunflower oils at 35 g/kg in corn-soybean diets to broiler breeders and found increased long chain omega 3 and omega 6 fatty acids in the meat. Supplementation with enzymes (Raza et al, 2009;Anuradha & Roy, 2015), amino acids (Kumar et al, 2016) and probiotics (FAO, 2016) is reported to improve poultry utilisation of high fibre diets. Raza et al (2009) observed improved fibre digestibility in sunflower based diets supplemented with NIBGE enzyme.…”
Section: Introductionmentioning
confidence: 99%